The Dilemma of Marriage Postponement among Final-Year Female Students at STDI: A Case Study from the Perspective of Islamic Family Law - Sabrina Rufaida; Sabilul Muhtadin (Rayah Al-Islam, 2026)
Final-year female students are frequently confronted with a dilemma between pursuing further education and entering the workforce, which leads them either to postpone marriage or to prioritize personal relationships through marriage. This phase represents a transitional period toward professional life. Balancing academic responsibilities and marital life simultaneously presents considerable challenges. This study aimed to analyze the factors contributing to the emergence of the dilemma of marriage postponement, the strategies employed by female students in coping with the resulting internal conflicts, the perspective of Islamic family law on this dilemma, and the influence of educational attainment on partner selection criteria. This research adopted a qualitative method with a case study approach focusing on final-year female students at the Sekolah Tinggi Dirasat Islamiyah Imam Syafi’i. Data were collected through in-depth interviews with research participants, and analyzed using the Miles and Huberman model. The findings revealed that: (1) there are four primary factors contributing to the dilemma of marriage postponement among the students; (2) four key strategies are employed by the students to cope with the internal conflict associated with postponing marriage; (3) the dilemma of marriage postponement is perceived as a test of faith; and (4) educational level significantly influences the criteria used in selecting a prospective spouse.